Exploring classes of cancer patient navigators and determinants of navigator role retention. (14th June 2022) - Garcia‐Alcaraz, Cristian; Roesch, Scott C.; Calhoun, Elizabeth; Wightman, Patrick; Mohan, Prashanthinie; Battaglia, Tracy A.; Cobian Aguilar, Rosa; Valverde, Patricia A.; Wells, Kristen J.; ,
Abstract : BACKGROUND: In the current nationwide study, the authors used latent class analysis (LCA) to identify classes of cancer patient navigators (CPNs) and examined whether class membership and 12 indicators were related to navigator role retention. METHODS: By using data from 460 CPNs in the United States, LCA identified classes (ie, homogenous subgroups) of CPNs with the following indicators: type of CPN (clinical vs nonclinical), education level, area(s) of the cancer care continuum in which the CPN provided patient navigation, region and urbanity where the CPN provided services, organizational work setting, and patient navigation program funding source. The associations of navigator retention with class membership and each indicator were examined using χ 2 tests. RESULTS: LCA identified 3 classes of CPNs. Classes 1 and 3 were conceptualized as distinct, homogeneous subgroups of clinical CPNs that appeared to differ mainly on their likelihood of engagement in outreach, survivorship, palliative care, and end‐of‐life patient navigation. Class 2 was conceptualized as a nonclinical CPN subgroup that was distinct primarily based on their high endorsement of employment in programs, which are at least partially funded by grants and engagement in earlier stages of patient navigation (eg, early detection). The provision of survivorship and treatment patient navigation was related to navigator role retention, with senior CPNs providing these patient navigation services more than novice CPNs. CONCLUSIONS: The current study highlights 3 distinct classes of CPNs, provides initial information regarding determinants of navigator retention, and makes several recommendations for future patient navigation research.